2006
DOI: 10.1021/ie060152o
|View full text |Cite
|
Sign up to set email alerts
|

Single-Phase and Two-Phase Base-Catalyzed Transesterification of Canola Oil to Fatty Acid Methyl Esters at Ambient Conditions

Abstract: Experiments were performed at ambient temperature to investigate mass transfer during the transesterification reaction of canola oil with methanol (MeOH) to form fatty acid methyl esters by use of a sodium hydroxide (NaOH) base catalyst. Reactions were conducted at two NaOH catalyst concentrations under quiescent conditions, agitated two-phase conditions, and agitated single-phase conditions that were achieved by the addition of a solvent, tetrahydrofuran. A MeOH to oil molar ratio of 6:1 was employed. Small c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
50
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 15 publications
1
50
0
Order By: Relevance
“…The use of a co-solvent to produce homogeneous feed solutions of a triglyceride and methanol has been examined (Ataya et al, 2006). Boocock et al (1996Boocock et al ( , 1998 and Mao et al (2004) suggested that the transesterification of triolein with alkaline catalysts was significantly enhanced by the addition of liquid co-solvents such as tetrahydrofuran (THF) and t-butyl ether.…”
Section: Introductionmentioning
confidence: 99%
“…The use of a co-solvent to produce homogeneous feed solutions of a triglyceride and methanol has been examined (Ataya et al, 2006). Boocock et al (1996Boocock et al ( , 1998 and Mao et al (2004) suggested that the transesterification of triolein with alkaline catalysts was significantly enhanced by the addition of liquid co-solvents such as tetrahydrofuran (THF) and t-butyl ether.…”
Section: Introductionmentioning
confidence: 99%
“…Mass-transfer limitations can be reduced by using cosolvents to give homogeneous reactions that are much faster. 6 This requires solvent distillation, a recycle loop, larger reactors to accommodate solvent, and more energy. Plus, the dilution itself reduces the ultimate reaction rate.…”
Section: Introductionmentioning
confidence: 99%
“…For example, advantages include production from renewable materials (oils, fats), low environmental burden and lower CO 2 emissions when is used normal biodiesel. On the other hand, production includes higher cost of some materials and there are higher nitrogen oxides emissions.Production is providing by a transesterification of free fatty acids (see Ataya et al, 2006;Canakci & Gerpen, 2001; Van Gerpen, 2005).Because the process was manually controlled and it was a lot of time consuming, It was designed a simple controlling system for production of biodiesel. It's based on programmable logic controller from SAIA Company.…”
mentioning
confidence: 99%